New or rare Madagascar tiger beetles—17. Description of Pogonostoma (Microstenocera) noheli sp. nov. and redescription of P. (M.) flavomaculatum W. Horn (Coleoptera: Cicindelidae) - Moravec, Jiří; Vybíra, Jan (Zootaxa, 2018)
Pogonostoma (Microstenocera) noheli sp. nov. from central-eastern Madagascar is described as new to science. The new species was previously (in the monograph of the genus by Moravec 2007) partly confused and included within the externally very similar P. (M.) flavomaculatum W. Horn, 1892, a hitherto rare species based on a holotype only. A rectified redescription of the genuine P. (M.) flavomaculatum also is presented, complemented with external and internal diagnostic characters gained from a great number of recently caught adults. A revised key to Pogonostoma (Microstenocera) pusillum species-group and illustrations of the habitus, diagnostic characters and variability of these two species are provided.